Принципи функціонально-просторової організації енергоефективного житла середньої поверховості в прибережних районах Ірану - Омід, Мораді Пур; Сьомка, Сергій; Omid, Moradi Pour; Sergey, Siomka (Видавництво Львівської політехніки, 2020)
Стаття присвячена принципам функціонально-просторової організації енергоефективного житла середньої поверховості в прибережних районах Ірану. Регіони Півдня і Півночі країни найбільш густозаселені, оскільки мають вихід до водної поверхні: на півночі до Каспію, на півдні – до Перської затоки. В роботі зроблено спробу систематизувати типологічний ряд житла середньої поверховості з енергоефективними технологіями з вбудованими, прибудованими, надбудованими та окремо розміщеними елементами енергоефективного обладнання. Окрім цього, в статті сформульовано основні та допоміжні принципи організації архітектурно-планувальної та об’ємно-просторової організації житла середньої поверховості з енергозберігаючим обладнанням

The article is devoted to the principles of functional and spatial organization of energy-efficient housing, architectural, artistic and compositional features of the organization of housing with energy-efficient technologies. The article deals with the issues of architectural planning and spatial modification of residential buildings of medium height depending on the natural and climatic conditions and features of the country's region. Special attention is paid to the regions where there are significant water resources. The Persian Gulf and the Caspian sea region in Iran are the most densely populated and represent areas where all four types of possible types of energysaving technologies are presented: solar, water, wind energy and energy from the earth's interior. According to the forecasts of the world's leading scientists, Iran will have significant problems both with providing drinking water and with providing residential buildings with heat and energy in the next 30 years, with a steadily growing population. National traditions in close contact with modern nanotechnologies will allow Iran to enter the top ten countries with the most advanced energy-saving technologies and provide practically waste-free technologies for the life cycle of both individual residential buildings and entire residential formations, residential neighborhoods and entire cities. Under the correct organization of a waste-free closed life cycle of a residential building, the efficiency of reuse of internal energy can reach 85–90 percent. The article covers in detail the possible typological features of the mutual placement of different types of medium-rise residential buildings in relation to energy-saving equipment: built-in, attached, superstructured and placed separately from the building (near or at a considerable distance). The author systematized and grouped residential buildings based on the architectural, artistic and compositional criteria into four large groups (according to planning composition): point-individual residential buildings of medium height, point sectional houses; linear-paired semi-detached residential buildings, semi-detached sectional residential buildings of medium height; perimeter residential buildings (squares) of medium height with a courtyard and with the characteristic national architecture of the perimeter development of residential neighborhoods. The author makes an attempt to systematize medium-rise housing with energy-saving technologies in Iran, depending on its typological features, planning structure and type of placement of energy-efficient equipment in relation to it.
Principles of functional and spatial organization of energy-efficient medium-rise housing in the coastal regions of Iran
Keywords: енергоефективне обладнання; житлові будинки середньої поверховості; принципи організації; архітектурно-планувальні особливості; енергоефективні технології; типологія житла з ЕЗО (енергозберігаючим обладнанням); energy-efficient equipment; medium-rise residential buildings; principles of organization; architectural and planning features; energy-efficient technologies; typology of housing with ESE (energy-saving equipment); 728.004.18